Three times negative 2 minus three is equal to -9
Three Times A Number x Minus Two translates to 3x-2 Three Times A Number x Minus Two translates to 3•x-2 Three Times A Number y Minus Two translates to 3y-2 Three Times A Number z Minus Two translates to 3z-2
If you mean: 6 times (3-3) plus 2 then the answer is 2
3*(-2) = -6
Four times 3^2 minus two = 34.
It is either 2|x| - 3 or 2|x-3| depending on if the minus three is part of the absolute value.
Three minus three times six plus two is equal to -13.
so, if 2 minus Ln times 3 minus x equals 0, then 2 minus Ln times 3 equals x, therefore 2 minus Ln equals x divided by three, so Ln + X/3 = 2 therefore, (Ln + [X/3]) = 1
7 times minus 2 =